Materials for electrical and electronic components and manufacturing method thereof
Patent Information
- Application Number
- JP2021053055
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-26
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2041-03-26
AI Technical Summary
【0011】 本発明によって、導電率および引張強さが高く、耐応力緩和特性(小さな応力緩和率)およびめっき密着性に優れた被膜を有する電気·電子部品用材料及び電気·電子部品用材料の製造方法を提供することができる。
Smart Images

Figure 0007630327000004 
Figure 0007630327000005 
Figure 0007630327000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a material for electric / electronic components and a method for producing a material for electric / electronic components. [Background technology]
[0002] Conventionally, the terminals of connectors, which are connecting parts for electric and electronic equipment, have been made of materials in which the surface of brass, phosphor bronze, or Corson alloy is underplated with Ni or Cu, and then plated with Sn or Sn alloy. However, in recent years, the drive system for automobiles and other devices has been shifting to electric vehicles to achieve fuel savings compared to gasoline, and the amount of current flowing through the wiring between the battery, inverter, and motor has increased dramatically. In addition, wiring and connecting parts for electric and electronic equipment in automobiles and other devices require materials for electric and electronic components that are high voltage and have conductivity that can withstand large currents.
[0003] Furthermore, in order to reduce the size and weight of electrical and electronic equipment connection parts, the cross-sectional area of materials for electrical and electronic components in current-carrying members tends to become smaller. However, as the cross-sectional area becomes smaller, there is a problem that the electrical resistance increases, heat generation increases when electricity is applied, and strength decreases. Therefore, high conductivity and tensile strength are required to correspond to high voltage, large current, and miniaturization.
[0004] Until now, materials for electrical and electronic components used at high voltages and large currents have often been made of copper alloys as spring materials with high electrical conductivity, and have a coating of Ag or Ag alloy plating, which also has high electrical conductivity. However, when exposed to high temperatures for long periods of time, the spring pressure decreases due to a decrease in tensile strength, which increases the contact resistance at the contact points and leads to further heat generation.Therefore, materials for electrical and electronic components are required to have high electrical conductivity, high tensile strength, and stress relaxation resistance that allows them to maintain their tensile strength even at high temperatures, as well as good plating adhesion that allows them to maintain a strong electrical connection without gaps (voids) between the materials for electrical and electronic components and the plating film.
[0005] Patent Document 1 discloses a copper alloy material that combines high electrical conductivity, tensile strength, and stress relaxation resistance by adding alloy elements to a Cu-Cr-based copper alloy, and Patent Document 2 discloses a copper alloy material that combines high electrical conductivity, tensile strength, and stress relaxation resistance by adding alloy elements to a Cu-Cr-Mg-based copper alloy for use as a terminal material. Patent Document 3 discloses a Cu-Mg-P based copper alloy Sn-plated sheet having a copper alloy sheet used for terminals and connectors as a base material, a processed altered layer on the surface thereof, and a plating layer consisting of a Sn phase, a Sn-Cu alloy phase, and a Cu phase in this order from the surface to the base material.
[0006] However, in Patent Documents 1 and 2, a heat treatment process after the final processing step is necessary to realize high stress relaxation resistance properties, but sufficient heat treatment causes a decrease in tensile strength and 0.2% yield strength, and there is a problem that the plating film is easily peeled off depending on the pretreatment method during plating. Furthermore, in Patent Document 3, there is a problem that the plating film is easily peeled off during the processing step during manufacturing and when used under stress due to the presence of a processing-affected layer. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 5307305 [Patent Document 2] Patent No. 6301734 [Patent Document 3] Patent No. 6055242 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a material for electric / electronic components having high electrical conductivity and tensile strength, and excellent stress relaxation resistance and plating adhesion, and a method for producing the material for electric / electronic components. [Means for solving the problem]
[0009] As a result of extensive investigations in order to achieve the above-mentioned object, the inventors have discovered a material for electric / electronic components having excellent stress relaxation resistance capable of being used for long periods of time at high temperatures, and a method for manufacturing a material for electric / electronic components, by removing a process-affected layer with fine crystal grains that has been caused by rolling and heat treatment on the surface of the material for electric / electronic components, making it difficult for the base material and the plating film to peel off from each other, and by adjusting the ratio (Dc / Ds) of the average grain size (Ds) of the crystal grains located in the central region of the cross section to the average grain size (Dc) of the crystal grains located in the surface layer region of the cross section, when viewed in a thickness direction cross section perpendicular to the rolling and stretching direction of the material for electric / electronic components, to be in the range of 0.9 to 1.1, thereby completing the present invention.
[0010] That is, the gist of the present invention is as follows. (1) A material for electric / electronic components comprising a Cu-based base material containing 0.10-0.50 mass% Cr and 0.01-0.50 mass% Mg, with the remainder being Cu and unavoidable impurities, and a coating made of a conductive material formed on at least a part of a surface of the Cu-based base material, the coating being composed of at least one layer and made of an Ag-based material containing 80 mass% or more of Ag, wherein the Cu-based base material has a ratio (Dc / Ds) of the average grain size (Dc) of crystal grains located in a central region of a cross section to the average grain size (Ds) of crystal grains located in a surface region of the cross section in a range of 0.9-1.1. (2) The material for electric / electronic parts according to the above (1), wherein the Cu-based base material further contains 0.01 to 0.50 mass % of Si. (3) The material for electric / electronic components according to (1) or (2) above, wherein the Cu-based base material further contains 0.05 to 0.50 mass % in total of at least one selected from the group consisting of Zn, Fe, Sn, Ag and Ni. (4) The material for electric / electronic components according to any one of (1) to (3) above, wherein the average grain size (Ds) of crystal grains located in the cross-sectional surface layer region of the Cu-based base material is 1 μm or more. (5) The material for electric / electronic parts according to any one of (1) to (4) above, wherein the coating has a thickness of 0.1 μm or more and 20 μm or less. (6) The material for electric / electronic parts according to any one of (1) to (5) above, further comprising an underlayer made of a Ni-based material between the surface layer and the Cu-based base material. (7) The material for electric / electronic components according to (6) above, further comprising an intermediate layer made of a Cu-based material between the surface layer and the underlayer. (8) A material for electric and electronic components according to any one of (1) to (7) above, which has an electrical conductivity of 65% IACS or more at 20°C, a tensile strength of 400 MPa or more at 20°C, and a stress relaxation rate of 25% or less when tested under conditions in which an initial load stress on the surface is 80% of the 0.2% yield strength and the material is maintained at 150°C for 1,000 hours. (9) A method for producing a material for electric / electronic components according to any one of (1) to (8) above, comprising the steps of melting and casting a Cu-based material having a similar composition to the Cu-based base material (step (1)), performing homogeneous heat treatment (step (2)), cooling after hot working (step (3)), performing cold working (step (4)), performing heat treatment (step (5)), performing finish cold working (step (6)), performing stress relief annealing (step (7)), degreasing with an alkaline solution (step (8)), dissolving and removing a work-affected layer accompanied by surface dissolution with an acid (step (9)), and forming the coating by plating (step (10)). Effect of the Invention
[0011] The present invention can provide a material for electric / electronic components having a coating that has high electrical conductivity and tensile strength, and is excellent in stress relaxation resistance (small stress relaxation rate) and plating adhesion, and a method for producing the material for electric / electronic components. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic cross-sectional view of a material for electric / electronic components according to one embodiment of the present invention. [Diagram 2] Figure 2 schematically shows a cross-section of a material for electrical and electronic components according to another embodiment of the present invention.
Embodiments for Carrying Out the Invention
[0013] Hereinafter, preferred embodiments of the present invention will be described in detail. [Material for Electrical and Electronic Components] The material for electrical and electronic components according to an embodiment of the present invention contains 0.10 to 0.50% by mass of Cr and 0.01 to 0.50% by mass of Mg, with the balance being a Cu-based substrate composed of Cu and inevitable impurities, and a film composed of a conductive material formed on at least a part of the Cu-based substrate and composed of at least one layer or more. The film is composed of at least one layer or more and is a material for electrical and electronic components composed of an Ag-based material containing 80% by mass or more of Ag. In the Cu-based substrate, the ratio (Dc / Ds) of the average grain size (Dc) of the crystal grains located in the central region of the cross-section to the average grain size (Ds) of the crystal grains located in the surface layer region of the cross-section in the cross-section of the material for electrical and electronic components is in the range of 0.9 to 1.1. Hereinafter, all elements use the symbols shown in the periodic table. In the present invention, "M-based" (when M is a kind of metal element) means that the metal element M is contained as a main component (preferably 80% by mass or more) in all the contained metal elements.
[0014] Hereinafter, each part of the material for electrical and electronic components of the present invention will be described in detail. Figure 1 schematically shows a cross-section of a material for electrical and electronic components according to one embodiment of the present invention. The material for electrical and electronic components 10 shown in Figure 1 is a film 15 made of a conductive material formed on at least a part of the contact portion of the Cu-based substrate 11 with respect to the mating terminal, on the surface of one or both sides of the Cu-based substrate 11 containing Cu as a main component, and shows a case where only the surface layer 12 containing Ag as a main component is laminated and formed.
[0015] <Cu-based Substrate> The Cu-based base material 11 contains Cu as the main component, 0.10 to 0.50 mass% Cr, 0.01 to 0.50 mass% Mg, and the remainder Cu and inevitable impurities. Furthermore, the Cu-based base material 11 preferably contains 0.01 to 0.50 mass% Si. Furthermore, it preferably contains 0.05 to 0.50 mass% in total of at least one selected from the group consisting of Zn, Fe, Sn, Ag, and Ni. By setting the content of these components within the specified range, it is possible to increase the tensile strength while providing high electrical conductivity, and improve the stress relaxation resistance.
[0016] The shape of the Cu-based substrate 11 may be appropriately selected depending on the application, and may be a strip, plate, bar, or wire. The thickness of the Cu-based substrate 11 in the plate form is not particularly limited, but is preferably 0.02 to 2.0 mm, and more preferably 0.15 to 0.5 mm.
[0017] (Cr:0.10~0.50% by mass) By precipitating Cr in the Cu alloy matrix, the tensile strength and stress relaxation resistance can be improved without lowering the electrical conductivity. In the present invention, Cr is contained in an amount of 0.10 to 0.50 mass%, preferably 0.15 to 0.40 mass%, and more preferably 0.20 to 0.35 mass%. If the Cr content is less than 0.10 mass%, the amount of Cr or a compound containing Cr in the Cu matrix is small, so that the effect of improving the tensile strength and stress relaxation resistance cannot be sufficiently obtained. If the Cr content is more than 0.50 mass%, problems such as a decrease in electrical conductivity, a decrease in tensile strength due to the generation of coarse compounds in the Cu matrix, and an adverse effect on the stress relaxation resistance occur.
[0018] (Mg:0.01~0.50% by mass) Mg acts as a solid solution element in the Cu matrix, thereby improving the tensile strength and stress relaxation resistance. In the present invention, Mg may be contained in an amount of 0.01 to 0.50 mass%, preferably 0.05 to 0.40 mass%, and more preferably 0.10 to 0.30 mass%. If the Mg content is less than 0.01 mass%, the effect of improving the tensile strength and stress relaxation resistance cannot be sufficiently obtained, and if it is more than 0.50 mass%, problems such as a decrease in electrical conductivity and an adverse effect on the stress relaxation resistance occur.
[0019] (Si:0.01~0.50% by mass) Since Si acts as a solid solution element in the Cu matrix and is a component that can improve tensile strength and stress relaxation resistance, the Cu-based base material preferably further contains 0.01 to 0.50 mass% Si, more preferably 0.05 to 0.40 mass%, and even more preferably 0.10 to 0.30 mass%. If the Si content is less than 0.01 mass%, the characteristic improvement effect is not sufficiently obtained, and if it is more than 0.50 mass%, problems such as a decrease in electrical conductivity and an adverse effect on stress relaxation resistance occur.
[0020] (Zn, Fe, Sn, Ag, Ni: at least one of 0.05 to 0.50 mass% in total) The Cu-based base material preferably further contains at least one selected from the group consisting of Zn, Fe, Sn, Ag, and Ni in a total amount of 0.05 to 0.50 mass%. By containing at least one of these components, the tensile strength is increased and the stress relaxation resistance property is improved due to the pinning effect of the crystal grains, and further, the electrical conductivity can be improved. In addition, material properties such as plating adhesion can be improved. If the total content of Zn, Fe, Sn, Ag, and Ni is less than 0.05 mass%, the effect of adding the metal elements is insufficient, and if the total content of Zn, Fe, Sn, Ag, and Ni is too much more than 0.50 mass%, problems such as a decrease in electrical conductivity, an adverse effect on the stress relaxation resistance property, and an increase in raw material costs occur. For this reason, the total content of at least one selected from the group consisting of Zn, Fe, Sn, Ag, and Ni is preferably 0.05 to 0.50 mass%, more preferably 0.05 to 0.40 mass%, and even more preferably 0.10 to 0.30 mass%.
[0021] (balance: Cu and unavoidable impurities) The remainder of the Cu-based base material 11 is made up of Cu and inevitable impurities. Incidentally, inevitable impurities are impurities that are present in the raw materials or that are inevitably mixed in during the manufacturing process, and are essentially unnecessary, but are permitted because they are present in trace amounts and do not affect the properties of the material. The remainder is Cu.
[0022] (Cu-based substrate composition) The material 10 for electric / electronic components of the present invention uses a highly conductive Cu-based alloy for the Cu-based base material 11, and thus can suppress heat generation even when a large current is passed through it. In addition, by using the material 10 for electric / electronic components having a Cu-based base material 11 with high tensile strength, it is possible to prevent a gap from being formed between the material 10 and the mating terminal, and to prevent the gap from widening. Furthermore, the material 10 for electric / electronic components of the present invention has excellent stress relaxation resistance and bending workability. These will be explained below.
[0023] (Grain size ratio of Cu-based substrate) The Cu-based base material 11 has a ratio (Dc / Ds) of the average grain size (Ds) of the crystal grains located in the cross-sectional surface region in a cross-section perpendicular to the thickness direction and the rolling or stretching direction of the material 10 for electric and electronic components, in the range of 0.9 to 1.1. The cross-sectional surface region refers to a depth region from the surface to 1 / 10 of the thickness of the Cu-based base material 11 in the cross-sectional depth direction from the surface of the Cu-based base material 11 from which the work-affected layer has been removed. The cross-sectional central region refers to a central region located approximately 1 / 2 in the cross-sectional depth direction from the surface of the Cu-based base material 11. When the Cu-based base material 11 is subjected to deformation stress, if the grain size ratio is large, the deformation state of the surface region and the central region will be different, and peeling of the Cu-based base material 11 and the coating 15 may occur. Therefore, the grain size ratio is set to a range of 0.9 to 1.1 by controlling the amount to be removed in the cross-sectional surface region. By adopting this particle size ratio, it is possible to suppress large differences in the amount of deformation of the terminal substrate 10 due to bending and the amount of expansion due to heat generation, thereby preventing peeling of the coating 15 and the occurrence of cracks in the coating 15 due to bending.
[0024] (Average crystal grain size of Cu-based substrate surface layer) Also, the average grain size (Ds) of the crystal grains located in the cross-sectional surface layer region of the Cu-based base material 11 is set to 1 μm or more. By setting the average grain size (Ds) of the crystal grains to 1 μm or more, the deformation of the Cu-based base material 11 is uniform regardless of the location on the surface, and the occurrence of partial differences in the amount of deformation is prevented. Furthermore, by setting the average grain size of the surface layer of the Cu-based base material to 1 μm or more, it is possible to improve the stress relaxation resistance characteristic when subjected to stress or heat. Also, it is possible to prevent peeling of the coating 15 and the occurrence of bending cracks in the coating 15 due to bending and heat generation.
[0025] <Coating> As shown in FIG. 1, a material 10 for electric / electronic components of the present invention has a coating 15 made of a conductive material formed on at least a part of the surface of a Cu-based base material 11 . In the embodiment shown in FIG. 1, the coating 15 is configured as a single layer, that is, the surface layer 12 made of an Ag-based material containing 80 mass % or more of Ag.
[0026] (surface) The surface layer 12 is formed of an Ag-based material, such as metallic Ag or an Ag alloy containing 80% by mass or more of Ag. Ag has high conductivity among metals and generates little heat when current is passed through it. In addition, it is not easily oxidized near room temperature and its conductivity is not easily reduced, so it is used as the surface layer 12 for high voltage and large current applications. The surface layer 12 made of an Ag-based material can reduce the dynamic friction coefficient, reduce electrical resistance due to contact, and increase conductivity even if it is only a part of the surface.
[0027] The Ag-based material of the surface layer 12 is not particularly limited as an alloy component, but Sn is most preferable. Since the Ag-Sn alloy has excellent electrical conductivity and high hardness, forming the surface layer 12 with the Ag-Sn alloy can reduce the dynamic friction coefficient. Furthermore, since the Cu present in the intermediate layer 14 or the Cu-based base material 11 is unlikely to diffuse into the Ag-Sn alloy even when heated, it is possible to suppress the decrease in electrical conductivity caused by Cu diffusing to the surface of the outermost layer 12 and oxidizing upon contact with the outside air.
[0028] The thickness of the surface layer 12 is preferably 0.1 μm or more and 20.0 μm or less. If it is 0.1 μm or more, the conductivity is stable, and if it is 20 μm or less, the effect is saturated and costs can be reduced. It is more preferable that it is 0.5 to 7.0 μm, and even more preferable that it is 1.0 to 5.0 μm. When the surface layer 12 has such a thickness, it has excellent conductivity and can suppress the occurrence of surface cracks due to bending processing.
[0029] Fig. 2 is a schematic diagram showing a cross section of a material for electric / electronic components 10 according to another embodiment of the present invention. The material for electric / electronic components 10 according to the embodiment shown in Fig. 2 further has, as a coating 15 on a Cu-based substrate 11, an underlayer 13 made of a Ni-based material between a surface layer 12 and the Cu-based substrate 11, and an intermediate layer 14 made of a Cu-based material between the surface layer 12 and the underlayer 13. That is, the coating 15 is formed of three layers, in which the underlayer 13, the intermediate layer 14, and the surface layer 12 are sequentially laminated on the Cu-based substrate 11.
[0030] (base layer) The underlayer 13 is made of a Ni-based material such as metal Ni or a Ni-based alloy. The Ni-based alloy includes, but is not limited to, Ni-P and Ni-Fe alloys. The Ni plating suppresses Cu diffusion from the Cu-based base material 11 and prevents the decrease in electrical conductivity due to Cu oxidation on the surface. The thickness of the underlayer 13 is not limited to, but is preferably 0.1 to 3.0 μm, and more preferably 0.3 to 2.0 μm. If the thickness is less than 0.1 μm, Cu diffusion cannot be prevented, and if the thickness exceeds 3.0 μm, the effect of preventing Cu diffusion becomes excessive and the electrical conductivity decreases.
[0031] Note that, instead of the Ni-based material, metallic Co or a Co-based alloy, or metallic Fe or an Fe-based alloy can be used for the underlayer 13 to obtain the same effect as the Ni-based material. The alloy elements of the Co-based alloy or the Fe-based alloy are not particularly limited.
[0032] (Middle class) The intermediate layer 14 is made of a Cu-based material such as metallic Cu or a Cu alloy. The Cu alloy is not particularly limited, but may be, for example, a Cu-Zn alloy. The intermediate layer 14 further improves the adhesion between the underlayer 13 and the surface layer 12, and can suppress heat generation during long-term continuous use of the material for electric / electronic components 10. The thickness of the intermediate layer 14 is not particularly limited, but is preferably, for example, 0.01 to 1.0 μm, and more preferably, 0.03 to 0.5 μm. If it is less than 0.03 μm, it is not possible to improve the adhesion between the Ag-based alloy and the Ni-based alloy, and if it exceeds 3.0 μm, the effect is saturated.
[0033] (Conductivity of materials for electrical and electronic components) Furthermore, the material 10 for electric / electronic components has a conductivity of 65% IACS or more at 20°C. This allows the material to have excellent electrical conductivity. Here, the electrical conductivity (IACS; International Annealed Copper Standard) can be obtained by measuring in a thermostatic chamber controlled at 20°C (±1°C) using a four-terminal method. High electrical conductivity can reduce heat generation due to current flow and prevent peeling between the Cu-based substrate 11 and the coating 15. Furthermore, the material 10 for electric / electronic components preferably has a conductivity of 70% IACS or more at 20°C and a conductivity of 40% IACS or more at 150°C. In particular, it is preferable that the electrical conductivity at high temperatures is high. This allows the amount of heat generation to be suppressed even during continuous use at high voltage and large current, and prevents peeling between the Cu-based substrate 11 and the coating 15.
[0034] (Tensile strength of materials for electrical and electronic components) Furthermore, the material 10 for electric / electronic components has a tensile strength of 400 MPa or more at 20°C. Preferably, the material 10 for electric / electronic components has a tensile strength of 350 MPa or more at 150°C. The temperature of the material 10 for electric / electronic components increases with continued use. In particular, when used in connectors for automobiles, etc., the material 10 for electric / electronic components is required to be able to be used stably even in an environment of 150°C. If the tensile strength at 150°C is 350 MPa or more, it can be used stably even in a high-temperature environment. Since the material 10 for electric / electronic components has a high tensile strength, it is possible to obtain a high strength even if the cross-sectional area of the material 10 for electric / electronic components is reduced, which enables the material for electric / electronic components to be miniaturized. Furthermore, since the tensile strength is high at high temperatures, the amount of heat generated can be suppressed even at high voltages and large currents, and it can be used stably.
[0035] (Stress relaxation resistance of materials for electrical and electronic components) Stress relaxation resistance is an index showing how much the springiness of a material weakens after it is subjected to a load within the elastic range where the material exhibits springiness (a load of 80% of 0.2% yield strength) and kept in a high-temperature environment at 150°C for 1000 hours, and is expressed as the stress relaxation rate when the initial load stress on the surface is left at 150°C for 1000 hours. This stress relaxation rate is 25% or less, and more preferably 20% or less. This prevents a decrease in tensile strength due to long-term use at high temperatures, and prevents an increase in contact resistance due to a decrease in contact pressure between terminals.
[0036] (Contact resistance of materials for electrical and electronic components) In addition, the material 10 for electric / electronic components of the present invention is placed in a high-temperature environment when used at high voltage and current, and is brought into contact with a mating terminal. Therefore, the material 10 for electric / electronic components of the present invention reduces the contact resistance when it contacts with a mating terminal in a high-temperature environment. Furthermore, the material 10 for electric / electronic components of the present invention has high tensile strength even in a high-temperature environment where the stress relaxation rate is large, and it is preferable that the stress relaxation rate at high temperatures is reduced.
[0037] (Temperature coefficient of resistance of materials for electrical and electronic components) The electrical / electronic component material 10 of the present invention has a temperature coefficient of resistance of 3700 ppm / °C or less in the range of 20°C to 150°C. The temperature coefficient of resistance is the magnitude of change in electrical resistance value due to temperature expressed in parts per million per degree C. The electrical / electronic component material 10 is required to have a small temperature coefficient of resistance even when the environmental temperature changes. In particular, since the electrical / electronic component material 10 of the present invention is used in a wide temperature range from room temperature to high temperatures, by setting the temperature coefficient to 3700 ppm / °C or less, it can be used stably even when the environmental temperature changes.
[0038] (Method of measuring temperature coefficient of resistance) A method for measuring the temperature coefficient of resistance will be described below. The temperature coefficient of resistance (TCR) was measured in the range of 20°C to 50°C by a method (four-terminal method) conforming to the methods specified in JIS C2525 and JIS C2526. Then, calculation was performed using the following formula (1). Formula (1): TCR(×10 -6 / K)=(RR 0 ) / R 0 ×1 / (TT 0 ) x 10 6 Here, T in formula (1) is the test temperature (℃), T 0 is the reference temperature (℃), R is the resistance value (Ω) at the test temperature T, R 0 is the test temperature T 0 The resistance value (Ω) at
[0039] (Plating adhesion of materials for electrical and electronic components) Furthermore, the surface layer of the material 10 for electric / electronic components of the present invention is made smooth and flat by dissolving and removing the process-affected layer, and by laminating and forming a coating 15 such as the surface layer 12 on top of this, it has excellent plating adhesion. Since there is little change in the surface layer caused by thermal expansion caused by use in high-temperature conditions accompanied by high voltage and large current, and by stress such as bending deformation when mated with a mating terminal, the plating adhesion between the surface layer of the material 10 for electric / electronic components and the coating 15 is excellent. As a result, heat generation can be suppressed even when high voltage and large current are passed through it.
[0040] (Bending cracks in plating on materials for electrical and electronic components) Furthermore, in the material 10 for electric / electronic components of the present invention, the process-affected layer is dissolved and removed to provide a smooth and flat state, and by laminating and forming a coating 15 such as the surface layer 12 on top of this, it is possible to suppress the occurrence of a difference in deformation between the bent part and other parts even when the material is subjected to bending, and it is possible to prevent the laminated coating 15 from peeling off from the Cu-based base material 11 or the coating 15 from cracking.
[0041] The material 10 for electrical and electronic parts of the present invention has high electrical conductivity and tensile strength, and is excellent in stress relaxation resistance and plating adhesion, and when used in contacts, it can ensure high initial contact pressure, and the amount of heat generated during current flow is small, and even if heat is generated, the spring pressure does not decrease much, so that high contact pressure can be maintained. In addition, the material has high electrical conductivity even in high-temperature environments such as automobiles, and has excellent plating adhesion, so that heat generation can be suppressed. For these reasons, the material is suitable for terminals of on-board parts that pass large currents, such as EVs and HEVs, connectors, lead frames, relays, switches, sockets, etc., for peripheral infrastructure and solar power generation systems, etc.
[0042] [Method of manufacturing materials for electrical and electronic components] Next, a preferred example of the manufacturing method of the terminal material of the present invention is shown below. The terminal material of the present invention is manufactured by sequentially carrying out the steps of melting and casting a Cu-based material having a composition similar to that of the Cu-based base material (step (1)), performing homogeneous heat treatment (step (2)), cooling after hot working (step (3)), performing cold working (step (4)), performing heat treatment (step (5)), performing finish cold working (step (6)), performing stress relief annealing (step (7)), performing degreasing with an alkaline solution (step (8)), performing dissolution and removal of the work-affected layer accompanied by surface dissolution with an acid (step (9)), and forming the coating by plating (step (10)). The cold working step (step (4)) and the heat treatment step (step (5)) may be performed multiple times. The manufacturing method will be described below.
[0043] (Step (1): Melting and casting) A Cu alloy that provides the Cu composition of a material for electric and electronic components is melted and cast in a melting furnace in a vacuum or inert gas atmosphere, and then cooled to obtain an ingot having a desired composition. Melting and casting can be performed by a known method.
[0044] (Step (2): Homogenization heat treatment) The homogenization heat treatment dissolves the compounds contained in the ingot in the Cu matrix, homogenizing the components of the ingot. This allows the added components to have a sufficient effect, and the variations in electrical conductivity, tensile strength, etc. in the Cu-based base material can be reduced. The manufacturing method of the present invention performs homogenization heat treatment at a temperature of 800 to 1000°C for 0.5 to 12 hours, more preferably at 900 to 1050°C, and even more preferably at 950 to 1050°C.
[0045] (Step (3): Hot processing) The ingot immediately after the homogenization heat treatment is hot worked, preferably hot rolled at 700 to 950°C to reduce the plate thickness, and then cooled. Cooling is performed, for example, by water cooling. If the cooling rate is too slow, some of the metal elements will precipitate during cooling, and the desired final properties will not be obtained.
[0046] (Step (4): Cold working) The material after hot working is cold worked (cold rolling, etc.) to work the plate material into the desired thickness. The working is carried out by rolling, etc.
[0047] (Step (5): Heat treatment) For materials after cold working, it is preferable to heat the material at 350 to 650°C for 10 minutes to 24 hours. Preferably, the aging precipitation heat treatment is performed at 400 to 650°C for 1 to 10 hours. This heat treatment causes fine precipitates to precipitate in the Cu matrix, improving the electrical conductivity, tensile strength, and stress relaxation resistance. When the treatment is performed at a low temperature for a short time, the amount of precipitates is small and the particle size of the precipitated compounds is too fine, so that the electrical conductivity, tensile strength, and stress relaxation resistance cannot be improved. When the treatment is performed at a high temperature for a long time, the precipitated compounds become coarse, improving the electrical conductivity, but not improving the tensile strength and stress relaxation resistance. In addition, the cooling rate to 300°C after the aging heat treatment is preferably 2°C / min or less. By setting the cooling rate to 300°C in this range, the electrical conductivity, tensile strength, and stress relaxation resistance can be further improved.
[0048] (Step (6): Finishing cold working) The material after the heat treatment is subjected to a finishing cold working (cold rolling, etc.) preferably at a working rate of 10 to 50%, more preferably 10 to 40%. In addition, by setting the upper limit of the cold working rate to 50% or less, mechanical properties such as stress relaxation characteristics can be set within the desired range. The finishing process improves the tensile strength and reduces the difference between the tensile strength and the 0.2% proof stress. If the finishing working rate is less than 10%, sufficient improvement in strength cannot be expected, and the difference between the tensile strength and the 0.2% proof stress becomes large. If the total working rate is more than 50%, the electrical conductivity, stress relaxation resistance characteristics, and bending workability are significantly reduced, and it becomes difficult to recover these characteristics and maintain the strength at the same time in the subsequent stress relief annealing process.
[0049] (Step (7): Strain relief annealing) By performing stress relief annealing on the material after the finish processing, the tensile strength decreases and the difference between the tensile strength and the 0.2% proof stress increases. However, the electrical conductivity, stress relaxation resistance, and bending workability are improved. In the present invention, stress relief annealing is performed at a temperature of 300 to 550°C for 2 to 60 s. The temperature is more preferably in the range of 350 to 500°C. The time is more preferably in the range of 3 to 20 s. In this case, the heating rate and cooling rate are preferably 50°C / s or more, and more preferably 100°C / s or more. When the material is treated at a low temperature for a short time, there is almost no change in the tensile strength, electrical conductivity, stress relaxation resistance, and bending workability. When the material is treated at a high temperature for a long time, the tensile strength decreases significantly and the difference between the tensile strength and the 0.2% proof stress increases. When the heating rate and cooling rate do not satisfy the specified range, even if the target values are obtained for the tensile strength, electrical conductivity, and stress relaxation rate, the difference between the tensile strength and the 0.2% proof stress increases. In addition, by carrying out the cold working in step (6) and the annealing for stress relief in step (7) within the specified ranges, the amount of remaining stress and precipitates can be controlled.
[0050] (Step (8): Degreasing) After stress relief annealing, the material is degreased. During hot and cold working, lubricants are supplied between the processing equipment and the material for electrical and electronic components, so these must be removed from the material for electrical and electronic components before the next process begins. If the material is not degreased, it will be impossible to uniformly remove the affected layer during dissolution in the next process. Mineral oil, synthetic oil, etc. are used as lubricants. Examples of degreasing methods include solvent degreasing and electrolytic degreasing. Alkaline degreasing uses inorganic components such as sodium hydroxide (NaCl) and sodium carbonate (Na 2 CO 3 ), sodium bicarbonate (NaHCO 3 ), Sodium phosphate (Na 2 PO 4 ), Sodium orthosilicate (Na 4 SiO 4 It is preferable to use an alkaline solution such as that prepared by
[0051] (Step (9): Removal of Process-Affected Layer) This is a process of dissolving and removing the degreased electric / electronic component material by using an acid, specifically, an acid that is soluble in the Cu-based base material (e.g., hydrofluoric acid, mixed acid, aqua regia, a mixture of sulfuric acid and hydrogen peroxide, etc.), which involves surface dissolution. The depth of surface dissolution can be appropriately determined according to the thickness of the processed layer. It is preferable to dissolve and remove at least 2 μm of the surface. As a method for dissolving and removing, either chemical polishing or electrolytic polishing can remove the processed layer without distorting the Cu-based base material. In addition, by dissolving and removing the surface layer of the Cu-based base material, the grain size ratio (Dc / Ds) can be set to a range of 0.9 to 1.1. In addition, the surface of the Cu-based base material after removal can be made smooth. As a result, a coating 15 with excellent plating adhesion and bending plating crack resistance can be obtained in the plating in the next step (9).
[0052] (Process-affected layer of Cu-based substrate) When manufacturing the Cu-based base material 11, a process-affected layer with fine crystal grains is always formed on the surface of the base material because the Cu-based material is melted and formed by applying heat and pressure. The fine crystal grains indicate that the strain due to the pressure applied by processing is large. Therefore, the process-affected layer is dissolved and removed by acid while dissolving the surface of the Cu-based base material 11 in a manner that does not cause strain. It is preferable to remove 2 μm or more of the process-affected layer by dissolving with acid. The amount to be dissolved is appropriately determined in consideration of the grain size ratio (Dc / Ds). In this way, by removing the process-affected layer, the surface and the inside of the Cu-based base material 11 are made homogenous, so that the bending workability of the material 10 for electric / electronic components is good and peeling between the Cu-based base material 11 and the coating 15 such as the surface layer 12 can be made less likely to occur. Similarly, in the case of high voltage and large current, the temperature coefficient of resistance of the material 10 for electric / electronic components can be improved.
[0053] (Step (10): Plating) In the plating process, a multi-layered plating layer is formed on a Cu-based substrate 11 in the following order: an underlayer 13 of a Ni-based plating layer, an intermediate layer 14 of a Cu-based material plating layer, and a surface layer 12 of an Ag-Sn alloy or the like. The method for forming each layer is not particularly limited, but examples thereof include wet plating such as electrolytic plating and electroless plating, and dry plating such as vapor deposition and sputtering. Among these, wet plating is preferred, and electrolytic plating is more preferred. In particular, a copper cyanide bath is electrodeposited from a solution containing copper cyanide complex ions and excess free alkali cyanide, and plating is performed under a higher overvoltage than an acid bath, resulting in a dense and uniform coating. EXAMPLES
[0054] Next, in order to further clarify the effects of the present invention, examples and comparative examples will be described, but the present invention is not limited to these examples.
[0055] The raw Cu alloy material was melted and cast to produce an ingot, which was then subjected to homogenization heat treatment, hot working, and water cooling. After water cooling, the oxide film of the material was removed by facing, followed by cold working, heat treatment at 350-650°C for 10 minutes to 24 hours, and cooling to 300°C at a cooling rate of 2°C / min. After cooling, finish rolling and stress relief annealing were performed in succession, and then degreasing with an alkaline solution and desmutting with an acid were performed, followed by Ag plating in an alkaline cyanide bath to obtain the desired material for electrical and electronic components. By keeping the conditions of each process within the specified range, a sample with the target material was obtained. In addition, materials with different components and manufacturing methods were produced as comparative examples.
[0056] Table 1 shows the component compositions of the Cu-based base materials of Examples 1-13 and Comparative Examples 1-12. The contents in Table 1 are all in mass%, with the remainder being Cu and unavoidable impurities. Additionally, (-) indicates that no addition was made, and the underlined parts indicate that the composition is outside the scope of the present invention. [Table 1]
[0057] Table 2 shows the composition of the materials for electric / electronic components of Examples 1 to 13 and Comparative Examples 1 to 12, including the surface dissolution amount of the material for electric / electronic components of the present invention, the grain size ratio between the surface layer and the center of the Cu-based base material and the average grain size of the surface layer, the type and thickness (μm) of the surface layer, the type and thickness (μm) of the underlayer, and the type and thickness (μm) of the intermediate layer. The materials for electric / electronic components are in the form of a plate, and the plate thickness is 0.3 mm. The plate thickness is not limited in the present invention. The underlined parts indicate that the thickness is outside the scope of the present invention. The method for measuring the film thickness is described below.
[0058] (Method of measuring surface layer thickness) The surface layer and thickness were calculated by SEM observation and EDX at arbitrary magnification from the cross section. To confirm the thickness of each layer, the thickness was also measured by image analysis on the cross section. The image analysis was performed according to the scanning electron microscope test method of JIS H8501:1999.
[0059] [Table 2]
[0060] Examples 1 to 13 of the present invention are within the range of the component composition of the material for electric / electronic components of the present invention, and conform to the manufacturing method of the present invention. Furthermore, the composition of Comparative Examples 1, 2, and 4 to 8 is outside the range of the material for electric / electronic components of the present invention. Comparative Examples 9 to 11 have the same composition as Invention Example 1, but the amount of work-affected layer removed shown in Table 2 is outside the range of the material for electric / electronic components of the present invention. In Comparative Example 12, the amount of work-affected layer removed is 0 μm, meaning that the work-affected layer was not removed. Furthermore, in Comparative Example 3, hot cracking occurred during production, making it impossible to evaluate the performance.
[0061] The following describes the performance evaluation of materials for electric / electronic components of Examples 1 to 13 and Comparative Examples 1 to 12. Table 3 shows the performance evaluation, including electrical conductivity at 20°C and 150°C, tensile strength at 20°C and 150°C, stress relaxation rate at 150°C / 1000h, contact resistance, plating adhesion, and plating bending cracks.
[0062] The measurement methods for the evaluation items are described in detail below.
[0063] (Method of measuring average crystal grain size and grain size ratio) The cross section perpendicular to the rolling direction of the material for electric and electronic components is polished to a mirror finish by wet polishing and electrolytic polishing to prepare a test piece, and the average grain size is calculated on the IPF image obtained using analysis software (TSL, OIM Analysis) from the crystal orientation data continuously measured using an EBSD detector attached to a high-resolution scanning analytical electron microscope (JEOL, JSM-7001FA) by a cut method conforming to JIS H 0501 (1986). The measurement is performed in each region with a step size of 0.1 μm, and grain boundaries are defined as orientation differences of 15° or more, and grains consisting of 2 pixels or more are the subject of analysis. Regarding the grain size ratio, the average grain size in each region is determined by the cut method, and the ratio is calculated.
[0064] (Method of measuring electrical conductivity) The electrical conductivity is expressed as the average value (%IACS) of the electrical conductivity measured for multiple plate materials in a thermostatic chamber controlled at 20℃ (±1℃) using the four-terminal method based on JIS H0505-1975. The distance between the terminals was 100 mm.
[0065] (Method of measuring tensile strength) Three JIS Z2201-13B test pieces cut from the test material (test piece) in the direction parallel to the rolling direction were measured in accordance with JIS Z2241:2011, and the average value was expressed.
[0066] (Method of measuring stress relaxation rate) Here, the stress relaxation ratio (SRR) can be measured according to the Japan Copper and Brass Association JCBA T309:2004 "Stress relaxation test method by bending copper and copper alloy thin plate strip" by the cantilever method (using a cantilever block jig) under the conditions of an initial load stress on the material surface of 80% of the 0.2% yield strength, and a temperature of 150°C for 1000 hours. The test piece is a rectangular shape with a width of 10 mm, and the rolling parallel direction and the length direction of the test piece are aligned. Before heat treatment, the position of the tip of the test piece when an initial stress of 80% of the yield strength is applied to the test piece held by a cantilever on the test stand is a distance δ from the reference position. 0 The specimen is placed in a thermostatic chamber at 150°C for 1000 hours (heat treatment of the specimen with initial stress applied). After the load is removed, the position of the tip of the specimen is a distance H from the reference position. t The position of the tip of the test piece when heat treatment is performed on the test piece without applying stress is at a height of H from the reference position. 1 From these relationships, the stress relaxation rate (%) is (H t -H 1 ) / (δ 0 -H 1 ) × 100.
[0067] (Contact resistance measurement) The contact resistance was measured by the four-terminal method using a measuring terminal that was contacted with a load of 1N and a current of 10mA was passed between the terminals. A TFF Keithley Instruments 6220 DC current source was used as the DC current source, and a current meter (the same company's 2182A nanovoltmeter) was used to measure the electrical resistance. The contact resistance was measured at five arbitrary points, and the average value (n=5) was calculated for each point and evaluated according to the following criteria. A contact resistance value of less than 10mΩ was marked as "◎", a contact resistance value of 10mΩ to less than 20mΩ was marked as "〇", a contact resistance value of 20mΩ or more was marked as "×", and a contact resistance value of 0 was marked as the plating peeled off. The cases that met the criteria of "◎" and "〇" were evaluated as being within the range where no problems would occur in actual use and were at the pass level.
[0068] (Method of evaluating plating adhesion) The adhesion of the surface treatment layer to the substrate was evaluated by carrying out a peel test on the test material (surface treatment material) prepared by the above-mentioned method. The peel test was carried out based on "15.1 Tape test method" of "Plating adhesion test method" specified in JIS H 8504:1999. The plated surface treatment is scratched at 2mm intervals with a cutter knife or the like, reaching the base material, and tape is applied to another base material and peeled off in one go to check whether the plating peeled off or not. The adhesion evaluation results are shown in Table 3. When no plating peeling was observed, it was marked as "Good", and when plating peeling was observed, it was marked as "Poor". When it was marked as "Good", it was evaluated as being within the range where no problems would occur even if it was actually used, and the plating adhesion was at an acceptable level.
[0069] (Method of evaluating plating bending cracks) The bending workability was evaluated by performing a V-bend test on the samples prepared by the above-mentioned method at a bending radius of 0.5 mm in a direction perpendicular to the rolling streak (rolling direction) under the condition of bending radius / sheet thickness = 1, and then observing the surface of the top part with a microscope (VHX200; Keyence Corporation) at an observation magnification of 200 times. The results are shown in Table 3. The bending workability shown in Table 3 was evaluated as "○ (good)" when no cracks were observed on the surface of the top part, and "× (not good)" when large cracks were observed. In addition, it was evaluated as "-" when the coating peeled off and no plating cracks could be observed. In this test, the cases corresponding to "○ (good)" were evaluated as being at an acceptable level of bending workability, as being within a range where no problems would occur even if actually used.
[0070] [Table 3]
[0071] (Evaluation Results) In the invention examples 1, 3, 5, and 11, the Cu-based alloy contains Cr, Mg, and Si as metal elements, and other properties such as electrical conductivity, tensile strength, stress relaxation rate, plating adhesion, and plating bending cracking were obtained without any practical problems. In the invention examples 2, 4, and 6, the metal elements Cr, Mg, and Si were contained, but even without the intermediate layer, practical results were obtained without any practical problems. In the invention example 7, the metal elements Cr and Mg are contained, and further Zn is contained, and the electrical conductivity, etc. are all within the ranges specified in the present invention, so that practical results were obtained without any practical problems. In the invention examples 8 and 10, the metal elements Cr and Mg are contained, and further Fe and Ag are contained, respectively, but even without the intermediate layer, practical results were obtained without any practical problems. In the invention example 9, the metal elements Cr and Mg are contained, and further Sn is contained, and the electrical conductivity, etc. are all within the ranges specified in the present invention, so that practical results were obtained without any practical problems. Examples 12 and 13 of the invention contain the metal elements Cr, Mg, and Si, and further contain Ni and Zn, respectively. Even though they lack both the undercoat layer and the intermediate layer and only have the surface layer, the electrical conductivity, etc. are all within the ranges specified by the present invention, and therefore no practical problems were observed.
[0072] In contrast, in Comparative Example 1, the tensile strength was low because the Cr content was low, although all other component compositions were within the ranges specified by the present invention. In Comparative Example 2, the stress relaxation rate was high because Mg was not contained. In Comparative Example 3, the Mg content was high, which caused hot cracks during production, and evaluation was not possible. In Comparative Example 4, the Zn content was high, the amount of dissolution to remove the work-affected layer was small at 0.5 μm, and the particle size ratio was large at 2.0, so the conductivity was low and the plating peeling occurred, and the plating adhesion was evaluated as "x". Similarly, in Comparative Example 5, the Fe content was high and the amount of dissolution to remove the work-affected layer was small at 0.5 μm, so the conductivity was low and the plating peeling occurred, and the plating adhesion was evaluated as "x".
[0073] In Comparative Examples 6, 7, and 8, the Cu-based substrate had a large Sn, Si, and Ni content, respectively, and the amount of dissolution to remove the work-affected layer was small at 0.5 μm. Although the plating layer did not peel off from the Cu-based substrate, cracks occurred in the plating film in the bending test, and the plating bending cracks were evaluated as "x". In Comparative Examples 9, 10, 11, and 12, the component composition was the same as that of Invention Example 1. In Comparative Example 9, the average crystal grain size of the surface layer was in the range of 1 μm or more, but the grain size ratio (Dc / Ds) was large at 1.6, the amount of dissolution to remove the work-affected layer was small, and the surface layer was thin, so that bending cracks occurred in the bending test, and the plating bending cracks were evaluated as "x". In Comparative Example 10, the grain size ratio (Dc / Ds) was large at 2.1, and the amount of dissolution to remove the work-affected layer was small, so that bending cracks occurred in the bending test. In Comparative Example 11, the grain size ratio (Dc / Ds) was large at 2, and the amount of dissolution to remove the work-affected layer was small, so bending cracks occurred in the bending test, and the plating bending cracks were evaluated as "x." In Comparative Example 12, the grain size ratio was large at 2, and the work-affected layer was not removed, so the plating peeled off, and the plating adhesion was evaluated as "x." [Explanation of symbols]
[0074] 10 Materials for electrical and electronic components 11 Cu base material 12 Surface layer 13 Base layer 14 Middle Class 15 Capsule
Claims
1. A Cu-based base material containing 0.10 to 0.50 mass% Cr and 0.01 to 0.50 mass% Mg, with the balance being Cu and unavoidable impurities; A coating made of a conductive material formed on at least a part of the surface of the Cu-based base material; having The coating is a material for electric / electronic components, which is composed of at least one layer and is made of an Ag-based material containing 80% by mass or more of Ag, The Cu-based base material is a material for electric / electronic components, in which a ratio (Dc / Ds) of an average grain size (Dc) of crystal grains located in a central region of a cross section of the material for electric / electronic components to an average grain size (Ds) of crystal grains located in a surface layer region of the cross section is in the range of 0.9 to 1.
1.
2. The material for electric and electronic components according to claim 1, wherein the Cu-based base material further contains 0.01 to 0.50 mass % of Si.
3. The material for electric and electronic parts according to claim 1 or 2, wherein the Cu-based base material further contains 0.05 to 0.50 mass% in total of at least one selected from the group consisting of Zn, Fe, Sn, Ag and Ni.
4. The material for electric and electronic components according to any one of claims 1 to 3, wherein the average grain size (Ds) of crystal grains located in the cross-sectional surface layer region of the Cu-based base material is 1 µm or more.
5. The material for electric / electronic parts according to any one of claims 1 to 4, wherein the coating has a thickness of 0.1 µm or more and 20 µm or less.
6. The material for electric / electronic parts according to any one of claims 1 to 5, further comprising an underlayer made of a Ni-based material between the surface layer and the Cu-based base material.
7. 7. The material for electric / electronic parts according to claim 6, further comprising an intermediate layer made of a Cu-based material between said surface layer and said underlayer.
8. Conductivity at 20°C is 65% IACS or more; A tensile strength at 20°C of 400 MPa or more, and The material for electric / electronic parts according to any one of claims 1 to 7, wherein the material has a stress relaxation rate of 25% or less when tested under conditions in which an initial load stress on the surface is 80% of 0.2% proof stress and the material is maintained at 150°C for 1000 hours.
9. A method for producing a material for electrical and electronic components according to any one of claims 1 to 8, comprising the steps of: A method for producing a material for electric / electronic components, comprising the steps of: melting and casting a Cu-based material having a similar composition to the Cu-based base material (step (1)); performing homogeneous heat treatment (step (2)); cooling after hot working (step (3)); performing cold working (step (4)); performing heat treatment (step (5)); performing finish cold working (step (6)); performing stress relief annealing (step (7)); degreasing with an alkaline solution (step (8)); dissolving and removing a work-affected layer accompanied by surface dissolution with an acid (step (9)); and forming the coating by plating (step (10)).
Citation Information
Patent Citations
Device for attaching and detaching cassette
JP1978007305A
Gear measuring device
JP1985055242A
Fuel control device for electronic fuel injection type engine
JP1988001734A
Copper alloy for lead material of semiconductor equipment
JP1988093835A
Copper alloy for electronic equipment
JP1988109130A